Scheduling algorithm for the picture configuration for secondary tasks of a digital human–computer interface in a nuclear power plant. (13th March 2020) - Zhang, Gang; Zhang, Xuegang; Luan, Yu; Jiang, Jianjun; Hu, Hong
Secondary tasks of a digital human–computer interface in a nuclear power plant increase the mental workloads of operators and decrease their accident performance. To reduce the adverse effects of secondary tasks on operators, a picture configuration scheduling algorithm of secondary tasks is proposed. Based on the research background and operator interviews, a scheduling algorithm process is established, and variables and constraint conditions of the scheduling process are defined. Based on the scheduling process and variables definitions, this article proposes a picture feature extraction method, a method for counting identical keywords, an arrangement method of queues in a buffer pool and a picture configuration scheduling algorithm of secondary tasks. The results of simulation experiments demonstrate that the algorithm realizes satisfactory performance in terms of the number of replacements, the average waiting time, and the accuracy.